2020
DOI: 10.1044/2020_aja-19-00076
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Audiology Procedures in Children With Down Syndrome

Abstract: Purpose Normative data regarding behavioral audiologic testing procedures are based upon the general population and often do not apply to children with Down syndrome (DS). Testing children with DS can be challenging, and outcomes may be unreliable due to their different cognitive demands and delays. The aim of this study was to assess optimal audiologic testing procedures for specific age groups of children with DS. Method This study used a retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…This issue may be somewhat mitigated by the use of physiologic measures (e.g., auditory brainstem response and otoacoustic emissions), but these procedures are prone to missing some of the above hearing profiles and may require sedation. Challenges in adhering to recommended pediatric audiology diagnostic practices seen here and for other studies ( Findlen and Schuller, 2020 ; Nightengale et al, 2020 ; Trudeau et al, 2021 ), suggests that there is a need for future research and clinical guidance to ensure equitable access for children who have developmental disabilities to a comprehensive hearing assessment in a timely manner.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This issue may be somewhat mitigated by the use of physiologic measures (e.g., auditory brainstem response and otoacoustic emissions), but these procedures are prone to missing some of the above hearing profiles and may require sedation. Challenges in adhering to recommended pediatric audiology diagnostic practices seen here and for other studies ( Findlen and Schuller, 2020 ; Nightengale et al, 2020 ; Trudeau et al, 2021 ), suggests that there is a need for future research and clinical guidance to ensure equitable access for children who have developmental disabilities to a comprehensive hearing assessment in a timely manner.…”
Section: Discussionmentioning
confidence: 90%
“…Compared to typically-developing, age-matched controls, laboratory studies using clinical methods have confirmed that fewer behavioral thresholds are obtained for infants and children who have multiple conditions ( Gans and Gans, 1993 ); 3- to 10-year-old children who have autism spectrum disorder (ASD; Tharpe et al, 2006 ); or 6- to 72-month-olds with DS ( Greenberg et al, 1978 ). Similarly, retrospective clinical studies confirm that children who have developmental disabilities are at risk for not obtaining behavioral thresholds ( Meagher et al, 2021 ; Trudeau et al, 2021 ), and thresholds were obtained from children who have DS at ages later than recommended ( Nightengale et al, 2020 ). We posit that it is difficult to measure behavioral thresholds in children who have developmental disabilities because clinical methods are based on assumptions of typical child development.…”
Section: Introductionmentioning
confidence: 96%
“…Documenting performance differences across masker types is expected to advance our theoretical understand of auditory development for children with developmental disabilities. Furthermore, the creation of clinical tools for monitoring hearing abilities in children with developmental disabilities is in critical need, as this population is at increased risk of hearing loss (e.g., Rosenhall et al 1999; Kreicher et al 2018) yet are difficult to test with present behavioral methods (e.g., Gans & Gans 1993; Nightengale et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…These subjective and objective methods for hearing loss screening present various challenges for patients with IDD. Patients may have difficulty communicating their experiences or understanding instructions related to the hearing screen, thus necessitating more objective measures [ 30 ]. Patients may have behavioral issues that can make it challenging to complete a hearing screen.…”
Section: Identification Of Hearing Lossmentioning
confidence: 99%